Redesain Rumah Sakit Umum Daerah (RSUD) Banyumas BerdasarkanPedoman Perancangan Rumah Sakit Peraturan Kementerian Kesehatan - Salma Ali; Ahmad Farkhan; Mohammad Muqoffa (ARSITEKTURA, 2019)
A hospital is a health care institution providing patient treatment, with a complex building system. In Indonesia, there is a regulation for hospital building system set by The Republic of Indonesia’s Minister of Health arranging laws on hospital zoning plan, patient flow management, room requirement and size spesification, and structural and utilities system plan. Banyumas Dictrict Hospital is classified as type B academic hospital established in 1925. In order to develop hospital facilities and increase hospital bed capacity, Banyumas District Hospital demands area expansion and new buildings construction. This periodical development leads tol building system problems as zoning, hospital entrance and accessibility, and building flow system. Banyumas District Hospital is in need of post-occupancy-evaluation which is used as redeseign method, with the intention of restoring hospital to the regulation on hospital building by Minister of Health. Redesign result realized through the processing siteplan design, building design, and material application.